Johannes Knudsen: Danish rebel. The life of N. F. S. Grundtvig - og Ernst Nielsen: N. F. S. Grundtvig. An american study - Prenter, Regin (Grundtvig-Studier, 1956)
Johannes Knudsen: Danish Rebel. The Life of N. F. S. Grundtvig — and Ernest Nielsen: N. F. S. Grundtvig. An American Study. By Regin Prenter. These two books are typically American, but at the same time dependent on the Danish Grundtvigian tradition and recent Danish research on the life and writings of Grundtvig, with which they are both completely familiar. The two books do not contribute anything fundamentally new to the understanding of Grundtvig, but their American background makes it possible for them — especially in the case of Knudsen — to take up an independent attitude towards the divergent interpretations of Grundtvig in Denmark. Knudsens book is a well-written biography, factual and critical, without any hagiographical tendencies. Two concluding chapters of a more systematic nature (on the Church and on the nature of man) seek to show Grundtvig’s significance for the modern age. In his interpretation of Grundtvig Knudsen adopts the point of view that 1832 does not mark any decisively new phase in Grundtvig’s development. The new ideas are latent in the old. Grundtvig’s understanding of man is conditioned by his unterstanding of Christianity; but this includes a high valuation of what is human as the presupposition for what is Christian. Nielsen’s book is planned as a systematic investigation with Grundtvig’s understanding of the reality of the Spirit as its central theme. Its main thesis is that Grundtvig’s view of life is historical in contradistinction to every metaphysical or specualtive interpretation of existence. This point of view is worked out in an interesting way, but one could have wished that the author could have gone more thoroughly into a critical appraisement of this historical interpretation of existence than the very limited space at his disposal has allowed him to do. Both books are very much in sympathy with their subject, and a feature which they have in common is that they see Grundtvig as an ecumenical figure, and for this reason they betray a marked repugnance towards any attempt at a sectarian glorification of Grundtvig. It is much to be desired that these two books may awaken new interest in Grundtvig in America. But in order that this should succeed fully they must be followed by translations of Grundtvig’s writings.